Ensino-aprendizagem de triângulo: um estudo de caso no Curso de Licenciatura em Matemática a Distância - Farias, Severina Andréa Dantas de (2014)
This paper presents the organization and analysis of a mathematics teaching proposal, related to the content of Triangles, applied to the Bachelor's Degree in Mathematics Distance from Federal University of Paraíba - UFPB, in the distance. For this, we take as theoretical basis Activity Theory elements, considering the specifics of distance education. We have adopted in our benchmark Aretio (2004; 2006);Van de Walle (2009), Veloso (2000), Vigotsky (2007), Galperin (2009) and Talizina (2000), among others, along with official documents such as Referenciais da Paraíba (PARAIBA, 2010) and the Parâmetros Curriculares Nacionais (BRASIL, 1997, 1998, 2000, 2006). Participated in the study 67 students of the 97 registered in 5th period of the Mathematics Degree in distance learning of the Universidade Federal da Paraíba, from 18 counties in the state. We adopted as the methodology of the study the descriptive and exploratory research, according to the study objectives. Regarding the acquisition and analysis of data, this study was characterized by being a case study which the main instruments were a semi-structured questionnaire, tasks designed by the researchers, educational workshops and a field diary. Throughout the process the students performed 23 tasks, containing a total of 73 questions, for seven months of planning, preparation, execution and evaluation of five steps that characterized the study: creation, material or materialized, external language, internal and mental language. Upon completion of the data analysis, we confirm our thesis that through oriented assimilation, based on an approximation of the Activity Theory, combined with a planned system we can enhance the teaching and learning of mathematics content for the students who participated in all stages of the study, being checked at the end of the study and after a certain time a greater retention of assimilation of action and the triangle concept, featuring a breakthrough in learning quality of the participants.